Metodologias de gestão de processos de negócio em Instituições de Ensino Superior públicas brasileiras: um estudo comparativo - Raíssa Yuri Hamanaka (2019)
The contemporaneity is marked by the existence of organizations that experience prominent problems: the uncontrolled and growing informational volume to be managed, the absence of an effective management of its business processes, the absence of a systemic view of its processes, activities and informational flows, the increase customer expectations, environment of continuous changes and increased competitiveness in the global market. In this search for greater efficiency and the increasing knowledge acquisition, and consequently, by maintaining the organization's competitiveness in the market, initiatives, tools, techniques and methodologies for improving business processes are being adopted. The early stage of implementation of business process management methodologies in educational institutions motivated the research, as well as the need to map BPM methodologies to facilitate their implementation by public higher education institutions (HEIs). The research problem seeks to answer: how is the implementation of BPM methodologies occurring by Brazilian public HEI? The excessive bureaucracy of the public service and the limited focus on meeting citizen demands justify the need to study BPM methodologies in the context of public organizations. The objective of the research is to evaluate the existing academic business process management methodologies in the literature, through the Content Analysis method. In order to do this, we searched the Capes Portal and the Capes Thesis and Dissertations Base in which were mapped 14 BPM methodologies applied in the context of Brazilian public HEI. The sample was described through a thematic categorical matrix derived from the Content Analysis and analyzes between steps of the different methodologies were made. This bibliographic review study aims to contribute theoretically to the methodological literature of the area and it is also hoped to facilitate the information professional performance in the implementation of BPM methodologies.